Implementation of Ecology-Based Islamic Religious Education in Maintaining Environmental Sustainability - Khairunnisa Khairunnisa; Andi Anirah; Nurul Hikmawati; Nasrul Nasrul (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to examine the role of Islamic Religious Education (PAI) in environmental conservation. The focus of the study includes planning the implementation of ecology-based PAI, as well as the opportunities and obstacles faced in its implementation. The method used is a literature study with a qualitative approach. Data were obtained from various relevant literature sources, such as books, journals, and scientific articles. The results of the study indicate that PAI plays a significant role in instilling environmental awareness through religious values such as responsibility as a caliph, prohibition of causing damage, and teachings on maintaining cleanliness and balance of nature. Strategies that can be implemented include integrating environmental values into teaching materials, using contextual learning methods, and cultivating a habit of caring for the environment. Implementing this strategy requires support from all parties, including teachers, schools, parents, and the community. Despite obstacles such as limited teacher knowledge and facilities, this strategy still offers significant potential to shape a generation that cares about environmental sustainability.